STRUCTURAL AND INTERPERSONAL ANTECEDENTS OF PERCEIVED TEAM EFFECTIVENESS IN CONSTRAINED-FUNCTIONING TEAMS: A CROSS-SECTOR EXAMINATION - Rani OKHOMINA (PT. Antis International Publisher, 2025)
Objective: Purpose: Despite limited research on teams functioning under constrained conditions, this study examines how role clarity, psychological safety, and accountability jointly associate with perceived team effectiveness across three UK sectors. Method: Design/methodology/approach: A cross-sectional survey of 690 employees across healthcare, service, and manufacturing sectors was analysed using Pearson correlations, one-way ANOVA, hierarchical multiple regression, and ANCOVA. Results: Findings: All three predictors were significantly associated with perceived team effectiveness. Role clarity showed the strongest association (β = .27), followed by psychological safety (β = .19) and accountability (β = .13), together explaining 22% of variance. Team learning behaviours contributed an additional 3% (ΔR² = .03). Psychological safety retained significance after ANCOVA adjustment, though with reduced effect size. Novelty: Originality: This study offers the first cross-sector examination of these antecedents within a constrained-functioning team context, integrating the IMOI framework to demonstrate their distinct, additive contributions to perceived effectiveness.